9th Congress on Electronic Structure: Principles and Applications (ESPA 2014) A Conference Selection from Theoretical Chemistry Accounts - Ruiz-Lopez, Manuel F.; Olivares del Valle, Francisco J. (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This volume collects research findings presented at the 9th Edition of the Electronic Structure: Principles and Applications (ESPA-2014) International Conference, held in Badajoz, Spain, on July 2-4, 2014. The contributions cover research work on theory, methods and foundations, materials science, structure and chemical reactivity as well as environmental effects and modelling. Originally published in the journal Theoretical Chemistry Accounts, these outstanding papers are now available in a hardcover print format, as well as a special electronic edition. This volume provides valuable content for all researchers in theoretical chemistry, and will especially benefit those research groups and libraries with limited access to the journal.